Education for All: Strengthening Social Behaviours of Students in Diversity and Inclusion-Based School - Mewangi, Adila Bunga; Masrukhi, Masrukhi; Atmaja, Hamdan Tri (Journal of Educational Social Studies, 2024)
The diversity in Indonesia necessitates educators to create an environment accommodating this diversity in schools. This goal aligns with making education a means for "learning to live together," which is essential in 21st-century education. This paper employs a qualitative approach and is located at SMP Tunas Global. This study examines students' social behaviour and the process of strengthening social behaviour in diversity-based and inclusive schools. The research is conducted at SMP Tunas Global, a school known for its diversity and inclusion. Data sources include interviews with six students with special needs and typical students fromgrades 7, 8, and 9, observation notes during learning and additional activities, and student enrolment documents. Field study results indicate a tendency for role and expressive behaviours among students within the inclusive environment. However, social relationships between students with special needs and typical students do not naturally form. The limitation of parental consent for some students' condition information hampers the implementation of certain personalized programs.